Optimising the FAST program for stroke prevention in rural communities: a literature review - Agustin, Tasya Nabila; Melizza, Nur; Nur Rohmah, Anis Ika; Dwi Marta, Ollyvia Freeska (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Stroke poses a major challenge for rural communities due to limited healthcare access, low awareness, and cultural barriers to prevention. The FAST method offers a promising approach to early stroke detection by integrating community empowerment and a Transcultural Nursing framework, ensuring cultural adaptability and acceptance. This study uses a literature review method with the PRISMA approach to gather and analyze data from health science journals published from 2019 to 2024, accessed from databases such as Neliti, PubMed, ScienceDirect, and ProQuest. The screening process resulted in 15 articles that met the criteria, focusing on research related to early stroke detection education using the FAST method in at-risk populations. Data collection methods involved a systematic search strategy based on Medical Subject Headings (MeSH) and literature analysis utilizing the Joanna Briggs Institute (JBI) instrument. Analysis of the 15 articles indicates that education using the FAST method significantly enhances community understanding of early stroke symptoms. Through various media, such as posters, leaflets, and animated videos, this intervention is well-received by people of diverse ages and cultural backgrounds. Several studies also demonstrate a significant increase in participants’ knowledge after participating in the education program, with p-values <0,05. The FAST method, adapted with a Transcultural Nursing approach, is effective in improving stroke awareness among rural communities. This educational initiative contributes to reducing mortality and disability rates due to stroke in areas with limited access to healthcare services.